Why Higher Education Should Have a Leftist Bias - Lazere, Donald; SpringerLink (Online service). (New York : Palgrave Macmillan US, 2013)
Presenting a thoughtful justification for the left in American education, Donald Lazere argues that to teach students rhetoric and critical thinking, key components of a humanist education, educators must discuss and teach students to grapple with the conservative bias in academia, the media, and politics that is considered to be the status quo.
Keywords: Science; Science; Science, general